CORRELATION BETWEEN PLATELET PARAMETERS AND THE SEVERITY OF PRIMARY OPEN ANGLE GLAUCOMA - Gunanegara, Abdi Sastra; Yuliawati, Putu; Kusumadjaja, I Made Agus (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesPrimary open angle glaucoma (POAG) is a chronic optic neuropathy characterized by slowlyprogressive visual function loss. Platelet activation as well as its interaction with vascularendothelium and plasma components, play an important role in the vascular pathophysiology ofPOAG. Platelet aggregation in glaucoma tends to increase. This change has negative impact on smallvessel circulation in the eye, such as branches of short ciliary arteries supplying the optic nerve. Inthis study, we will assess the correlation between platelet parameters and the severity of POAG. MethodsThis study is an analytical observational study. Data were obtained retrospectively and prospectivelywith a cross sectional study approach conducted at Sanglah Hospital, Denpasar. The study samplewas 62 eyes selected consecutively. Data was analyzed using SPSS. Descriptive data presentednumerically or categorically, bivariate analysis using Pearson and Spearman correlation tests andmultivariate analysis using logistic regression. ResultsResults showed that the mean age of the research subjects was 66.71 ± 9.795 years, with themajority was male (70.6%). Bivariate analysis, showed no significant correlation between plateletparameters (PLT, PDW, MPV) and the severity of POAG. Multivariate analysis found that age ? 68years, 9,850 times more likely to develop moderate to severe glaucoma, compared to patients < 68years old (OR 9,850, 95% CI, p = 0.009). ConclusionPlatelet parameters showed no significant correlation with the severity of POAG, meanwhile olderage is more at risk of developing moderate to severe POAG.